Search for continuous gravitational waves from neutron stars in globular cluster NGC 6544 - Abbott, B. P.; Davies, G. S.; LIGO Scientific Collaboration and Virgo Collaboration (American Physical Society, 2017)
We describe a directed search for continuous gravitational waves in data from the sixth initial LIGO science run. The target was the nearby globular cluster NGC 6544 at a distance of ≈2.7  kpc. The search covered a broad band of frequencies along with first and second frequency derivatives for a fixed sky position. The search coherently integrated data from the two LIGO interferometers over a time span of 9.2 days using the matched-filtering F-statistic. We found no gravitational-wave signals and set 95% confidence upper limits as stringent as 6.0×10⁻²⁵ on intrinsic strain and 8.5×10⁻⁶ on fiducial ellipticity. These values beat the indirect limits from energy conservation for stars with characteristic spin-down ages older than 300 years and are within the range of theoretical predictions for possible neutron-star ellipticities. An important feature of this search was use of a barycentric resampling algorithm which substantially reduced computational cost; this method is used extensively in searches of Advanced LIGO and Virgo detector data.